Mary Macarthur's election manifesto, 1918 (page 1) (1918)
1918 1918-1939 "Mary Macarthur's election manifesto, 1918 (page 1)" [T0250.jpg], 1918 Mary Macarthur, secretary of the National Federation of Women Workers, stood as Labour Party candidate in Stourbridge, Worcestershire at the General Election on 14 December, 1918.